1998
DOI: 10.1177/016235329802100306
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Current Legislative and Policy Trends in Gifted Education: Life after the National Excellence Report

Abstract: Recent reports on the existence and nature of educational programs for gifted learners have indicated that current educational practices in gifted education vary in both availability and quality. One such report, National Excellence: A Case for Developing America's Talent (U.S. Department of Education, U.S. DOE, 1993), identified critical issues and established 7 initiatives for the improvement of the education of gifted students. This study examined the nature and availability of state legislative and policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…But, however long and laborious the passage of a law or other policy may be, its passage is best viewed as a milestone in a much longer journey. Implementation of the policy, careful review of its intended and unintended consequences, and revision of that policy are part of a never-ending cycle (see Landrum, Katsiyannis, & DeWaard, 1998; Swanson, 2007). A good recent example is the reauthorization of the Elementary and Secondary Education Act at the federal level, also known as the Every Student Succeeds Act (ESSA).…”
Section: Areas In Need Of Additional Policy Researchmentioning
confidence: 99%
“…But, however long and laborious the passage of a law or other policy may be, its passage is best viewed as a milestone in a much longer journey. Implementation of the policy, careful review of its intended and unintended consequences, and revision of that policy are part of a never-ending cycle (see Landrum, Katsiyannis, & DeWaard, 1998; Swanson, 2007). A good recent example is the reauthorization of the Elementary and Secondary Education Act at the federal level, also known as the Every Student Succeeds Act (ESSA).…”
Section: Areas In Need Of Additional Policy Researchmentioning
confidence: 99%
“…Moreover, their definitions of these terms, particularly "policy," reflected at least partial confusion, and their findings were not differentiated by source or by state. Similarly, Landrum, Katsiyannis, and DeWaard (1998) surveyed the state directors for gifted education, using a relatively short questionnaire and requesting supporting materials for three items: legislation, funding sources, and current initiatives or trends. They obtained completed questionnaires from 40 states and supplemental documentation from only 31 states.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quality of gifted education varied with the state policy intensities in USA when measured against the seven improvement initiatives suggested in the report National Excellence: A Case for Developing America's Talent (U.S. Department of Education, U.S. DOE, 1993), according to the studies by Landrum, Katsiyannis, and DeWaard (1998). Based on an analysis of state and local advocacies for gifted education and their outcomes, Robinson and Moon (2003) observed that collaborative, persistent advocates, who are also knowledgeable about best practices in gifted education and political processes at both local and state levels, presence of a champion, solving skills and tools for practical problem-solving skills of advocates were required for positive outcomes of gifted education.…”
Section: Gifted Education Service Delivery-role Of Principals and Teamentioning
confidence: 99%